Studying the effect of Political Relations on Capital Structure and Profit Sharing Policy of Companies Listed in Tehran Stock Exchange - MIR, AMIR; SOTUDEH, REZA; MALEKI, ESMAEIL (The journal of contemporary issues in business and government, 2021)
The purpose of this study is to investigate the effect of political relations on the capital structure and profit distribution policy of companies listed on the Tehran Stock Exchange during the years 2014 to 2020. Since the results of this research can be used by auditing organizations, auditing firms, researchers, students and companies, in terms of categorization of research in terms of purpose, it is of the type of applied research and in terms of classification of research in terms of method is causal after occurrence. The data collection tools in this research are scientific articles and Rahavard Novin software using information companies. Data analysis was performed using Ives software. The statistical population in this study is all companies listed on the stock exchange, of which 94 companies were selected as a sample through screening. The results showed that there is a significant relationship between the political relations of the parliament and the political relations of the government with financial leverage. Because the probability value of each of these variables is less than the standard value of 0.05%. The results also showed that there is a significant relationship between the political relations of the parliament and the political relations of the government and the policy of profit sharing. Because the probability value of each of these variables is less than the standard value of 0.05%.